2019
DOI: 10.21873/anticanres.13179
|View full text |Cite
|
Sign up to set email alerts
|

Nitrotyrosine (NT), a Nitrosative Stress Biomarker, Plasma Concentrations in Gallstone Disease and Cancer Patients

Abstract: Background/Aim: The aim of this study was to assess the plasma concentration of the nitrosative stress biomarker nitrotyrosine (NT) in gallstone disease and cancer patients. Materials and Methods: Initially, 114 patients with symptomatic gallstone disease were randomized into the laparoscopic cholecystectomy (LC) (n=54) and the minicholecystectomy (MC) (n=60) groups. The plasma concentrations of NT were measured just before, immediately after (POP1) and 6 h after operation (POP2). The cancer patients of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Accordingly, we and others have repeatedly shown that compared to the classic open approach, robot-assisted colorectal surgery is associated with attenuated inflammatory and beneficial immune response, which translates into favorable clinical outcomes [58][59][60][61][62][63]. No significant difference in plasma 3-NT with respect to the invasiveness of the procedure observed here is in line with previous observations concerning minilaparotomy cholecystectomy and laparoscopy cholecystectomy [64]. The 3-BT displayed distinct dynamics depending on the presence of serious postoperative complications and surgical site infections.…”
Section: Discussionsupporting
confidence: 91%
“…Accordingly, we and others have repeatedly shown that compared to the classic open approach, robot-assisted colorectal surgery is associated with attenuated inflammatory and beneficial immune response, which translates into favorable clinical outcomes [58][59][60][61][62][63]. No significant difference in plasma 3-NT with respect to the invasiveness of the procedure observed here is in line with previous observations concerning minilaparotomy cholecystectomy and laparoscopy cholecystectomy [64]. The 3-BT displayed distinct dynamics depending on the presence of serious postoperative complications and surgical site infections.…”
Section: Discussionsupporting
confidence: 91%
“…It is formed as a result of nitration of tyrosine phenolic units in tissues and proteins of the blood, contributing to increased susceptibility of proteins to the action of proteolytic enzymes. In addition, tyrosine nitration leads to the loss of biological functions of these proteins, and as a consequence, to pathological changes [33][34][35]. The high concentrations of total NO, accompanied by unchanged NT concentrations, determined in the serum of patients with mandibular fractures indicate that this molecule does not participate in the oxidative modification of proteins.…”
Section: Discussionmentioning
confidence: 99%
“…It is formed as a result of nitration of tyrosine phenolic units in tissues and proteins of the blood, contributing to increased susceptibility of proteins to the action of proteolytic enzymes. In addition, tyrosine nitration leads to the loss of biological functions of these proteins, and as a consequence, to pathological changes [34][35][36]. The high concentrations of total NO, accompanied by unchanged NT concentrations, determined in the serum of patients with mandibular fractures indicate that this molecule does not participate in the oxidative modification of proteins.…”
Section: Discussionmentioning
confidence: 99%